Maximizing Returns in Real-Time. - Fredrickson, Erika (Architectural Record, 2023)
The BIM work process, coupled with innovative developments in design software, enables real-time collaboration among all project stakeholders. BIM ON THE RISE: THE MAGIC OF COLLABORATIVE MODELING Building information modeling (BIM) is an intelligent software modeling process supported by a variety of tools and technologies. Modern design software has evolved way past the point of simple 2D and 3D renderings.